Value of C-Reactive Protein as a Risk Factor for Acute Coronary Syndrome: A Comparison with Apolipoprotein Concentrations and Lipid Profile. (16th October 2012) - Krintus, Magdalena; Kozinski, Marek; Stefanska, Anna; Sawicki, Marcin; Obonska, Karolina; Fabiszak, Tomasz; Kubica, Jacek; Sypniewska, Grazyna
Abstract : Objective . To investigate whether assessment of C-reactive protein (CRP) and apolipoproteins, besides the traditional lipid profile, enhances the assessment process for the risk of acute coronary syndrome (ACS). Methods . The study group consisted of 220 consecutive patients admitted to hospital within the first 6 hours from the onset of chest pain. Patients were diagnosed with unstable angina (n = 96 ), non-ST-elevation myocardial infarction (NSTEMI; n = 57 ), or ST-elevation myocardial infarction (STEMI; n = 67 ). ACS patients were compared with 116 healthy volunteers in a case-control study. The serum was assayed on admission for CRP, apolipoproteins ApoAI and ApoB100, and lipid parameters. Results . The highest concentrations of CRP were found in NSTEMI and STEMI, with a median value four-fold higher in ACS patients than in controls (P < 0.0001 ). Only CRP significantly increased the probability of ACS development (adjusted odds ratio for a 1 mg/L increase 1.90; 95% confidence interval [CI] 1.34–2.89) and explained 90% of the variation for ACS development. Similarly, we demonstrated the highest diagnostic accuracy for CRP among all investigated markers (area under the curve 0.80; 95% CI 0.75–0.85). Conclusions . Our study indicates that CRP superiorly to apolipoproteins and lipid profile facilitates the risk stratification for ACS occurrence.